Relationship between type of unprovoked venous thromboembolism and cancer location: An individual patient data meta-analysis. Issue 176 (April 2019) - Jara-Palomares, L.; van Es, N.; Praena-Fernandez, J.M.; Le Gal, G.; Otten, H.M.; Robin, P.; Piccioli, A.; Lecumberri, R.; Religa, P.; Rieu, V.; Rondina, M.; Beckers, M.; et al.
Abstract: Background: Unprovoked venous thromboembolism (VTE) may be the first manifestation of an underlying cancer. We aimed to assess the period prevalence of occult cancer detection stratified by VTE location (deep vein thrombosis [DVT], pulmonary embolism [PE] or both) and the anatomical relationship between occult cancer and VTE. Methods: Post-hoc analysis of a systematic review and individual patient data meta-analysis of adults with unprovoked VTE with at least 12 months of follow-up. Cancer types were grouped according to thoracic, abdomino-pelvic, or other locations. Results: A total of 2300 patients were eligible including 1218 with DVT only (53%), 719 with PE only (31%), and 363 with both PE and DVT (16%). The pooled 12-month period prevalence of cancer in DVT only, PE only, and DVT + PE was 5.6% (95% CI, 4.4 to 7.2), 4.3% (95% CI, 2.7 to 6.9), and 5.6% (95% CI, 1.7 to 15.5), respectively. Most occult cancers were located in the abdomen (68.4%). The proportion of patients with an abdomino-pelvic cancer was not different in patients with DVT + PE (81%; 95% CI, 54 to 96) than in those with DVT (68%; 95% CI, 57 to 78) or PE alone (65%; 95% CI, 48 to 79). Conclusion: The 12-month prevalence of occult cancer was similar in patients with DVT only, PE only, or both. Most cancers were located in the abdomen, and there was no relationship between VTE type and cancer location. Highlights: The relationship between sites of VTE and occult cancer is unclear. The 12-month prevalence of occult cancer was similar in DVT only, PE only, or both. There were no relationship between unprovoked VTE and occult cancer locations. Two thirds of cancers diagnosed after unprovoked VTE were located in the abdomen.